Economic resilience: what role for policies? - Caldera Sánchez, Aida (OECD Publishing, 2015)
The global financial crisis highlighted the importance of strengthening the resilience of our economies to adverse shocks. In this paper, we take stock of studies carried out primarily within, but also outside the OECD, to better understand the role of macroeconomic and structural policies in spurring or mitigating the vulnerabilities that can lead to costly shocks, as well as the role of policies in mitigating the shock impact and speeding the recovery. Then we offer tentative insights on how policies can be geared to address vulnerabilities early on, mitigate the impact of shocks and speed recoveries, as well as highlight possible trade-offs that exist across policy areas
Keywords: Economics